High-temperature qualitative curcumin-embedded slow-release Pickering emulsion and preparation method thereof

By using chitosan-octenyl succinate-sodium starch-sodium tripolyphosphate ternary composite nanoparticle stabilizers, a high-temperature precipitated curcumin-encapsulated sustained-release Pickering emulsion was prepared. This solved the problems of uneven dispersion and insufficient stability of curcumin in aqueous systems, achieving efficient encapsulation and slow release of curcumin and improving its absorption efficiency in the human body.

CN121370769APending Publication Date: 2026-01-23CHANGCHUN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511872923.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-12
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Curcumin is unevenly dispersed in aqueous systems, sensitive to ultraviolet light and high temperatures, and has low absorption efficiency in the human body, which prevents it from fully realizing its functional value. Existing Pickering emulsions have insufficient stability and poor sustained-release performance.

Method used

A high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion was prepared by using chitosan-octenyl succinate-sodium starch-sodium tripolyphosphate ternary composite nanoparticles as stabilizers to form a network structure through electrostatic interactions, hydrogen bonds and hydrophobic interactions, thereby optimizing the oil phase fraction and preparation process.

Benefits of technology

It significantly improves the stability of the emulsion and the encapsulation rate of curcumin, inhibits its degradation under high temperature and ultraviolet light, realizes the slow release of curcumin in simulated gastric juice, and improves bioavailability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121370769A_ABST
    Figure CN121370769A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature qualitative curcumin-embedded slow-release Pickering emulsion and a preparation method thereof. The curcumin-embedded slow-release Pickering emulsion is prepared from a water phase, an oil phase and curcumin, the water phase comprises chitosan-starch sodium octenylsuccinate-sodium tripolyphosphate ternary composite nanoparticles, and the mass fractions of chitosan, starch sodium octenylsuccinate and sodium tripolyphosphate in water in the ternary composite nanoparticles are respectively 1%, 0.84% and 0.08%; the oil phase is corn oil, soybean oil or rapeseed oil, and the volume fraction of the oil phase is 50%; chitosan, starch sodium octenylsuccinate and sodium tripolyphosphate are adopted to prepare ternary composite nanoparticles as a Pickering emulsion stabilizer, through electrostatic interaction, hydrogen bond and hydrophobic interaction, the composite particles form a net-shaped vein structure with dense pores, the adsorption capacity of the particles on an oil-water interface is remarkably improved, and the stability of the Pickering emulsion is improved. Therefore, the physical and chemical stability of the emulsion is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of curcumin-encapsulated sustained-release Pickering emulsion technology, specifically to high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion and its preparation method. Background Technology

[0002] Curcumin is a natural polyphenolic compound extracted from the rhizome of the turmeric plant. It possesses significant antioxidant, anti-inflammatory, and anti-tumor physiological activities. According to the assessment of the U.S. Food and Drug Administration (FDA), curcumin has extremely low toxicity and remains safe for humans even at a high daily intake of 12 grams. It has broad application prospects in the fields of food and health products and drug development.

[0003] However, the physicochemical properties of curcumin severely limit its practical application. On the one hand, curcumin has extremely poor water solubility, making it difficult to disperse uniformly in aqueous systems; on the other hand, it is sensitive to ultraviolet light and high temperatures, and is prone to decomposition and inactivation during processing and storage; at the same time, curcumin has low absorption efficiency and low bioavailability in the human gastrointestinal tract. These defects prevent its functional value from being fully realized.

[0004] Pickering emulsions are a class of emulsion systems stabilized by solid particles instead of traditional surfactants. They feature controllable particle size distribution, simple preparation methods, and excellent stability, which primarily depends on the physicochemical properties of the solid particles. Traditional inorganic surfactants often possess a degree of toxicity, failing to meet safety requirements in the food and pharmaceutical industries. Therefore, the use of biomacromolecules (such as proteins, polysaccharides, cellulose, and starch) as solid particle stabilizers has become a research hotspot. These biomacromolecules are not only safe and non-toxic but also enable the delivery and loading of functional components, while simultaneously addressing the problems of poor stability, weak sustained-release capacity of active ingredients, and rapid digestion rates inherent in traditional emulsions.

[0005] However, Pickering emulsions stabilized by single biomolecule particles are prone to stratification and lack stability. To improve this issue, researchers have used modification and compounding methods to utilize the interactions between two or more macromolecules to form complexes as stabilizers. For example, Ho et al. used pea protein and sodium caseinate as emulsifiers to prepare lycopene-loaded emulsions using high-pressure microfluidic technology, which maintained good stability and high lycopene retention after 14 days. Chen et al. found that emulsions prepared from whey protein isolate and gum arabic Maillard products exhibited excellent stability and significantly improved the bioavailability of β-carotene.

[0006] Chitosan, as a natural cationic polysaccharide, possesses good biocompatibility and biodegradability. However, single chitosan particles are highly hydrophilic, limiting their ability to stabilize Pickering emulsions. Sodium octenyl succinate starch (SSOS) is a commonly used food-grade emulsion stabilizer with some hydrophobicity. Sodium tripolyphosphate (TPP), as a cross-linking agent, can undergo ionic cross-linking reactions with chitosan. Currently, research on Pickering emulsions stabilized by chitosan-sodium octenyl succinate starch-sodium tripolyphosphate (CS-SSOS-TPP) ternary composite nanoparticles for curcumin encapsulation and sustained release has made some progress. However, the related preparation process has not yet formed a standardized and systematic technical solution, and the emulsion's high-temperature stability, resistance to environmental interference, and sustained-release performance still need further optimization to meet the needs of industrial production and practical applications.

[0007] Therefore, based on existing research, this invention provides a high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion and its preparation method. By optimizing the ratio of ternary composite stabilizers and the preparation process, and controlling key parameters such as the oil phase fraction of the emulsion, the stability, curcumin encapsulation rate, and sustained-release effect of the emulsion are significantly improved, providing technical support for the widespread application of curcumin in the food and pharmaceutical fields. Summary of the Invention

[0008] The purpose of this invention is to provide a high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion and its preparation method, so as to solve the problems mentioned in the background art.

[0009] To achieve the above objectives, the present invention provides the following technical solution: a high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion, composed of an aqueous phase, an oil phase, and curcumin;

[0010] The aqueous phase contains chitosan-octenyl succinate starch sodium-tripolyphosphate ternary composite nanoparticles, wherein the mass fractions of chitosan (CS), octenyl succinate starch sodium (SSOS), and tripolyphosphate (TPP) in the ternary composite nanoparticles in water are 1%, 0.84%, and 0.08%, respectively.

[0011] The oil phase is corn oil, soybean oil or rapeseed oil, and the volume fraction of the oil phase is 50%.

[0012] The curcumin is dissolved in the oil phase, and the concentration of curcumin in the oil phase is 300-700 mg / L;

[0013] The emulsion is an O / W type emulsion with an average droplet size of 3.8±0.17μm and a curcumin retention rate of ≥70% after 30 days of storage.

[0014] Preferably, the degree of deacetylation of the chitosan is ≥85%, and the purity of the curcumin is ≥95%.

[0015] The contact angle of the ternary composite nanoparticles is 91.3±3.05°, and the microstructure is a network of relatively dense pores.

[0016] The curcumin release rate of the emulsion was <20% after digestion in simulated gastric juice (SGF) for 120 min; and curcumin was slowly released after digestion in simulated intestinal juice (SIF) for 180 min.

[0017] The emulsion exhibits resistance to changes in the ionic environment. Within the NaCl concentration range of 0.1–0.5 mol / L, the emulsion droplets maintain regular morphology, good centrifugal stability, and still exhibit elastic behavior.

[0018] The emulsion is pH responsive, exhibits good stability under acidic conditions, and its structure is easily disrupted in neutral or alkaline environments.

[0019] A method for preparing a high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion includes the following steps:

[0020] Step 1: Preparation of chitosan-octenyl succinate starch sodium-tripolyphosphate ternary composite nanoparticle dispersion;

[0021] Step 2: Prepare the oil phase for dissolving curcumin;

[0022] Step 3: Mix the ternary composite nanoparticle dispersion with the oil phase containing dissolved curcumin, and then emulsify and homogenize to obtain Pickering emulsion;

[0023] Step 4: Store the prepared emulsion at 4°C in the dark.

[0024] Preferably, step one specifically includes the following operations:

[0025] (1) Weigh the set amount of chitosan, dissolve it in a 2% (v / v) acetic acid solution, and stir until completely dissolved to obtain a cationic chitosan solution;

[0026] (2) Under ultrasound-assisted conditions, the SSOS solution of the set concentration was slowly added dropwise to the chitosan solution above. After the addition was completed, stirring was continued for 10 min.

[0027] (3) Slowly add a TPP solution of a set concentration to the mixed solution, and after the addition is completed, sonicate for 30 min to obtain a ternary composite nanoparticle dispersion of colloidal dispersion system;

[0028] (4) The particle size, particle size distribution and zeta potential of the nanoparticles were determined by using a zeta potential and particle size analyzer to ensure that the performance of the nanoparticles met the requirements.

[0029] Preferably, step two specifically includes the following operations:

[0030] (1) Add powdered curcumin to corn oil, soybean oil or rapeseed oil so that the concentration of curcumin in the oil phase reaches 300-700 mg / L;

[0031] (2) Place the mixture on a magnetic stirrer and stir for 6 hours to fully dissolve the curcumin;

[0032] (3) Place the stirred mixture into a centrifuge and centrifuge to remove undissolved curcumin;

[0033] (4) Transfer the clear upper layer of the oil phase containing dissolved curcumin to a brown glass bottle and store it in the dark.

[0034] Preferably, step three specifically includes the following operations:

[0035] (1) The ternary composite nanoparticle dispersion was mixed with the oil phase containing curcumin at a volume fraction of 50% to obtain a mixed system.

[0036] (2) Place the mixture into a high-speed shear emulsifier and stir and disperse at 12000 rpm for 2 minutes to achieve preliminary emulsification;

[0037] (3) The pre-emulsified system was transferred to a homogenizer and homogenized at 13,000 rpm for 2 min to obtain a Pickering emulsion containing curcumin.

[0038] (4) The particle size distribution of the emulsion droplets was determined by a laser nanoparticle size analyzer, and the micromorphology and interface structure of the emulsion were observed by an optical microscope and a confocal laser scanning microscope (CLSM).

[0039] (5) By dropping a drop of emulsion into deionized water, stirring and observing the diffusion of the droplet, the emulsion is determined to be an O / W type emulsion.

[0040] Preferably, in step four, samples are taken periodically during the storage of the emulsion, and the concentration of curcumin is determined by spectrophotometry to calculate the curcumin retention rate;

[0041] The preparation method further includes a characterization step of the emulsion properties, specifically including:

[0042] (1) The turbidity of the composite particles was determined at 600 nm using a UV-1800 spectrophotometer;

[0043] (2) The contact angle of the composite particles was determined using a droplet shape analysis system (DSA100);

[0044] (3) The infrared spectrum of the nanoparticles was analyzed using a Fourier transform near-infrared spectrometer, with a scanning range of 4000–250 cm⁻¹. -1 32 scans, 4cm resolution -1 ;

[0045] (4) The composite particles were analyzed by XRD using an X-ray diffractometer (UltimaIV), with a scanning range of 5° to 60° and a scanning speed of 0.05° / min;

[0046] (5) The microstructure of the composite particles was observed using a scanning electron microscope (PhenomXL) with an accelerating voltage of 10kV.

[0047] (6) The rheological properties of the emulsion were analyzed using a rheometer with shear rates ranging from 0.1 to 100 s⁻¹. -1 The frequency scanning range is 0.1~10Hz, and the test temperature is 25±0.1℃.

[0048] (7) The centrifugal stability of the emulsion was determined by centrifugation. The emulsion was centrifuged at 5000 r / min for 10 min and the centrifugal stability index ES was calculated.

[0049] (8) The sustained-release performance of the emulsion was evaluated using an in vitro digestion model. The emulsion was incubated in simulated gastric juice (SGF, pH 1.2) and simulated intestinal juice (SIF, pH 6.8), and the amount of curcumin released was measured periodically.

[0050] (9) The antioxidant properties of the emulsion were determined by the DPPH method. The absorbance was measured at 517 nm and the DPPH free radical scavenging rate was calculated.

[0051] Compared with the prior art, the beneficial effects of the present invention are:

[0052] This invention uses chitosan, sodium octenyl succinate starch, and sodium tripolyphosphate to prepare ternary composite nanoparticles as Pickering emulsion stabilizers. Through electrostatic interactions, hydrogen bonds, and hydrophobic interactions, the composite particles form a network structure with dense pores, which significantly improves the adsorption capacity of the particles at the oil-water interface and thus enhances the physicochemical stability of the emulsion.

[0053] The emulsion prepared by this invention has excellent resistance to changes in ionic environment and pH responsiveness. It can maintain structural stability under different salt concentration conditions, has good stability in acidic environments, and can adapt to complex processing and storage environments, thus broadening its application scenarios.

[0054] This emulsion has a highly efficient encapsulation and protection effect on curcumin, effectively inhibiting the degradation of curcumin under high temperature, ultraviolet light and during storage, significantly improving the storage stability and antioxidant activity of curcumin, and extending the product shelf life.

[0055] The emulsion of the present invention exhibits good sustained-release properties during simulated digestion, which can protect curcumin from the destruction of simulated gastric juice and realize the slow release of curcumin in simulated intestinal juice, which is beneficial to improving the absorption efficiency of curcumin in the intestine and significantly improving its bioavailability. Attached Figure Description

[0056] Figure 1 The particle size (A) and potential (B) of the nanoparticles with different CS concentrations in this invention are shown.

[0057] Figure 2 The turbidity of each substance before and after the composite in this invention is shown in (A); the turbidity of the composite CS-SSOS-TPP at different pH values ​​is shown in (B).

[0058] Figure 3 The contact angles of the substances before and after composite formation in this invention;

[0059] Figure 4 The infrared spectrum (A) and XRD (B) of each substance before and after composite formation in this invention are shown.

[0060] Figure 5 SEM images of the substances before and after composite formation in this invention;

[0061] Figure 6 The average particle size (A), centrifugal stability (B), microstructure (C), static rheological diagram (D), and dynamic rheological diagram (E) of the emulsions with different oil phase fractions of the present invention are shown.

[0062] Figure 7 The images show the microstructure (A), centrifugal stability (B), static rheological diagram (C), and dynamic rheological diagram (D) of the emulsions at different NaCl concentrations according to the present invention.

[0063] Figure 8 The images show the microstructure (A), centrifugal stability (B), static rheological diagram (C), and dynamic rheological diagram (D) of the emulsion at different pH values ​​of this invention.

[0064] Figure 9 This is a CLSM image of the CS-SSOS-TPP nanoparticle-stabilized Pickering emulsion of the present invention;

[0065] Figure 10 The static rheological diagram (A), dynamic rheological diagram (B), microstructure diagram (C), and particle size distribution diagram (D) of the emulsions with different curcumin contents of the present invention are shown.

[0066] Figure 11 Storage stability of curcumin in this invention (A); Storage stability of curcumin at different concentrations in emulsion (B);

[0067] Figure 12 The antioxidant properties of curcumin at different concentrations in the emulsion of this invention (A); the antioxidant properties of the emulsion with an initial curcumin concentration of 500 mg / L over time (B);

[0068] Figure 13 This is a diagram showing the release characteristics of curcumin in simulated gastric and intestinal fluids according to the present invention. Detailed Implementation

[0069] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0070] Please see Figure 1-13 The present invention provides a high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion, which is composed of an aqueous phase, an oil phase and curcumin;

[0071] The aqueous phase contains chitosan-octenyl succinate starch sodium-tripolyphosphate ternary composite nanoparticles, wherein the mass fractions of chitosan (CS), octenyl succinate starch sodium (SSOS), and tripolyphosphate (TPP) in the ternary composite nanoparticles in water are 1%, 0.84%, and 0.08%, respectively.

[0072] The oil phase is corn oil, soybean oil, or rapeseed oil, and the volume fraction of the oil phase is 50%.

[0073] Curcumin is soluble in the oil phase, and the concentration of curcumin in the oil phase is 300-700 mg / L.

[0074] The emulsion is an O / W type emulsion with an average droplet size of 3.8±0.17μm. After 30 days of storage, the curcumin retention rate is ≥70%.

[0075] The degree of deacetylation of chitosan is ≥85%, and the purity of curcumin is ≥95%.

[0076] The contact angle of the ternary composite nanoparticles is 91.3±3.05°, and the microstructure is a network of relatively dense pores.

[0077] After digestion in simulated gastric juice (SGF) for 120 min, the curcumin release rate was <20%; after digestion in simulated intestinal juice (SIF) for 180 min, curcumin was slowly released.

[0078] The emulsion exhibits resistance to changes in the ionic environment. Within the NaCl concentration range of 0.1–0.5 mol / L, the emulsion droplets maintain regular morphology, good centrifugal stability, and still exhibit elastic behavior.

[0079] Emulsions are pH responsive, exhibit good stability under acidic conditions, but their structure is easily disrupted in neutral or alkaline environments.

[0080] A method for preparing a high-temperature qualitative curcumin-encapsulated sustained-release Pickering emulsion includes the following steps:

[0081] Step 1: Preparation of chitosan-octenyl succinate starch sodium-tripolyphosphate ternary composite nanoparticle dispersion;

[0082] Step 2: Prepare the oil phase for dissolving curcumin;

[0083] Step 3: Mix the ternary composite nanoparticle dispersion with the oil phase containing dissolved curcumin, and then emulsify and homogenize to obtain Pickering emulsion;

[0084] Step 4: Store the prepared emulsion at 4°C in the dark.

[0085] Step one specifically includes the following operations:

[0086] (1) Weigh the set amount of chitosan, dissolve it in a 2% (v / v) acetic acid solution, and stir until completely dissolved to obtain a cationic chitosan solution;

[0087] (2) Under ultrasound-assisted conditions, the SSOS solution of the set concentration was slowly added dropwise to the chitosan solution above. After the addition was completed, stirring was continued for 10 min.

[0088] (3) Slowly add a TPP solution of a set concentration to the mixed solution, and after the addition is completed, sonicate for 30 min to obtain a ternary composite nanoparticle dispersion of colloidal dispersion system;

[0089] (4) The particle size, particle size distribution and zeta potential of the nanoparticles were determined by using a zeta potential and particle size analyzer to ensure that the performance of the nanoparticles met the requirements.

[0090] Step two specifically includes the following operations:

[0091] (1) Add powdered curcumin to corn oil, soybean oil or rapeseed oil so that the concentration of curcumin in the oil phase reaches 300-700 mg / L;

[0092] (2) Place the mixture on a magnetic stirrer and stir for 6 hours to fully dissolve the curcumin;

[0093] (3) Place the stirred mixture into a centrifuge and centrifuge to remove undissolved curcumin;

[0094] (4) Transfer the clear upper layer of the oil phase containing dissolved curcumin to a brown glass bottle and store it in the dark.

[0095] Step three specifically includes the following operations:

[0096] (1) The ternary composite nanoparticle dispersion was mixed with the oil phase containing curcumin at a volume fraction of 50% to obtain a mixed system.

[0097] (2) Place the mixture into a high-speed shear emulsifier and stir and disperse at 12000 rpm for 2 minutes to achieve preliminary emulsification;

[0098] (3) The pre-emulsified system was transferred to a homogenizer and homogenized at 13,000 rpm for 2 min to obtain a Pickering emulsion containing curcumin.

[0099] (4) The particle size distribution of the emulsion droplets was determined by a laser nanoparticle size analyzer, and the micromorphology and interface structure of the emulsion were observed by an optical microscope and a confocal laser scanning microscope (CLSM).

[0100] (5) By dropping a drop of emulsion into deionized water, stirring and observing the diffusion of the droplet, the emulsion is determined to be an O / W type emulsion.

[0101] In step four, samples are taken periodically during the storage of the emulsion, and the concentration of curcumin is determined by spectrophotometry to calculate the curcumin retention rate.

[0102] The preparation method further includes a characterization step of the emulsion properties, specifically including:

[0103] (1) The turbidity of the composite particles was determined at 600 nm using a UV-1800 spectrophotometer;

[0104] (2) The contact angle of the composite particles was determined using a droplet shape analysis system (DSA100);

[0105] (3) The infrared spectrum of the nanoparticles was analyzed using a Fourier transform near-infrared spectrometer, with a scanning range of 4000–250 cm⁻¹. -1 32 scans, 4cm resolution -1 ;

[0106] (4) The composite particles were analyzed by XRD using an X-ray diffractometer (UltimaIV), with a scanning range of 5° to 60° and a scanning speed of 0.05° / min;

[0107] (5) The microstructure of the composite particles was observed using a scanning electron microscope (PhenomXL) with an accelerating voltage of 10kV.

[0108] (6) The rheological properties of the emulsion were analyzed using a rheometer with shear rates ranging from 0.1 to 100 s⁻¹. -1 The frequency scanning range is 0.1~10Hz, and the test temperature is 25±0.1℃.

[0109] (7) The centrifugal stability of the emulsion was determined by centrifugation. The emulsion was centrifuged at 5000 r / min for 10 min and the centrifugal stability index ES was calculated.

[0110] (8) The sustained-release performance of the emulsion was evaluated using an in vitro digestion model. The emulsion was incubated in simulated gastric juice (SGF, pH 1.2) and simulated intestinal juice (SIF, pH 6.8), and the amount of curcumin released was measured periodically.

[0111] (9) The antioxidant properties of the emulsion were determined by the DPPH method. The absorbance was measured at 517 nm and the DPPH free radical scavenging rate was calculated.

[0112] Example:

[0113] I. Experimental Materials and Instruments

[0114] 1. Experimental Materials

[0115] Chitosan (degree of deacetylation ≥ 85%); sodium octenyl succinate starch (SSOS) were purchased from Beijing Cargill Asia Pacific Food Systems Co., Ltd.; sodium tripolyphosphate (TPP) was analytical grade; curcumin (purity ≥ 95%) was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; glacial acetic acid was purchased from Tianjin Bohua Chemical Technology Co., Ltd.; corn oil was food grade; DPPH and ABTS were purchased from Aladdin Chemical Co., Ltd.; hydrochloric acid, sodium hydroxide, sodium chloride, pepsin, pancreatin, bile salts, sodium dihydrogen phosphate, disodium hydrogen phosphate, etc., were all analytical grade; the experimental water was deionized water.

[0116] 2. Experimental Apparatus

[0117] Zeta potential and particle size analyzer; UV-1800 spectrophotometer (Kyoto, Japan); droplet shape analysis system (DSA100). Germany); Fourier transform near-infrared spectrometer; X-ray diffractometer (Ultima IV, Rigaku, Japan); Scanning electron microscope (Phenom XL, Femto & Nano, China); Laser nanoparticle size analyzer (BT-90, Better, China); High-speed shear emulsifier; Homogenizer; Magnetic stirrer; Centrifuge; Rheometer (equipped with 40mm plate clamp); Optical microscope; Olympus IX-83 fluorescence microscope (Olympus, Tokyo, Japan); Laser confocal microscope (Zeiss 780, Germany); Thermostatic magnetic stirrer; Dialysis bags (molecular weight cutoff 14kDa); Spectrophotometer.

[0118] II. Preparation of High-Temperature Qualitative Curcumin Encapsulated Sustained-Release Pickering Emulsion

[0119] 1. Preparation of ternary composite nanoparticle dispersion

[0120] (1) Accurately weigh 1.0 g of chitosan and add it to 100 mL of 2% (v / v) acetic acid solution. Place it on a magnetic stirrer and stir for 3 h until the chitosan is completely dissolved to obtain a 1% cationic chitosan solution.

[0121] (2) Accurately weigh 0.84g of SSOS, add it to 100mL of deionized water, stir to dissolve and obtain a 0.84% ​​SSOS solution by mass.

[0122] (3) Accurately weigh 0.08g TPP, add it to 100mL of deionized water, stir to dissolve and obtain a TPP solution with a mass fraction of 0.08%;

[0123] (4) Place the chitosan solution in an ultrasonic cleaner, turn on the ultrasonic assistance, and slowly add the SSOS solution to the chitosan solution through a constant pressure dropping funnel at a dropping rate of 1 mL / min. After the addition is complete, continue stirring for 10 min to allow the two to react fully.

[0124] (5) Keeping the ultrasonic state unchanged, the TPP solution is slowly added to the above mixed solution through a constant pressure dropping funnel at a dropping rate of 0.5 mL / min. After the addition is completed, continue ultrasonic treatment for 30 min to obtain the CS-SSOS-TPP ternary composite nanoparticle dispersion of the colloidal dispersion system.

[0125] (6) Take a small amount of dispersion and use a Zeta potential and particle size analyzer to determine the particle size, particle size distribution and Zeta potential of the nanoparticles. Take three measurements and take the average value to ensure that the particle size distribution of the nanoparticles is uniform and the potential meets the stability requirements.

[0126] 2. Preparation of the oil phase for dissolving curcumin

[0127] (1) Weigh 30mg, 40mg, 50mg, 60mg and 70mg curcumin powder respectively and add them to 100mL of corn oil to obtain oil phase systems with curcumin concentrations of 300mg / L, 400mg / L, 500mg / L, 600mg / L and 700mg / L.

[0128] (2) Place the above oil phase systems on a magnetic stirrer and stir at 500 r / min for 6 h at room temperature to fully dissolve curcumin;

[0129] (3) Place the stirred oil phase systems into a centrifuge and centrifuge at 8000 r / min for 10 min to remove undissolved curcumin precipitate;

[0130] (4) Transfer the clear upper layer of the oil phase containing dissolved curcumin to five brown glass bottles, seal them, and store them in a dark place for later use.

[0131] 3. Preparation of Curcumin-encapsulated sustained-release Pickering emulsion

[0132] (1) Take 5 portions of 100 mL each of CS-SSOS-TPP ternary composite nanoparticle dispersion and place them in 5 250 mL beakers respectively;

[0133] (2) Add 100 mL of oil phase with different concentrations of curcumin-dissolved oil phase to the above beakers according to the oil phase volume fraction of 50% to obtain 5 oil-water phase mixed systems;

[0134] (3) Each mixture is placed into a high-speed shear emulsifier in sequence and stirred and dispersed at a speed of 12000 rpm for 2 minutes to carry out preliminary emulsification and obtain a primary emulsion;

[0135] (4) Each primary emulsion was transferred to a homogenizer and homogenized at 13,000 rpm for 2 min to obtain 5 Pickering emulsions with curcumin concentrations of 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L and 700 mg / L respectively.

[0136] (5) Take a small amount of emulsion, drop it into deionized water, stir it and observe that the droplet spreads rapidly. The emulsion is determined to be an O / W type emulsion.

[0137] (6) The five portions of the emulsion were placed into sealed containers, labeled, and stored in a refrigerator at 4°C away from light.

[0138] III. Performance Characterization of Emulsions and Composite Particles

[0139] 1. Performance characterization of nanoparticles

[0140] (1) Particle size and Zeta potential: The particle size, particle size distribution and Zeta potential of the CS-SSOS-TPP ternary composite nanoparticles were measured using a Zeta potential and particle size analyzer. The measurements were taken three times and the average value was taken. The results showed that the nanoparticles had a uniform particle size distribution, and the potential reached its highest value when the CS concentration was 1 mg / mL, which met the stability requirements.

[0141] (2) Turbidity determination: The absorbance of the composite particle dispersion was measured using a UV-1800 spectrophotometer at a wavelength of 600 nm in a 1 cm quartz tube. Each sample was measured five times, and the average value was taken. The results showed that the turbidity of the CS-SSOS binary complex was 0.101±0.002. After the addition of TPP, the turbidity of the ternary composite particles increased significantly to 0.179±0.007, indicating that CS and TPP interacted.

[0142] (3) Contact angle measurement: The freeze-dried CS, CS-SSOS, and CS-SSOS-TPP composite particle powders were compressed at 15 MPa for 1 min to form 13 mm × 2 mm thin films. The thin films were immersed in corn oil, and 2 μL of deionized water was added to the surface of the thin films using a syringe. After equilibration, the droplet image was captured, and the profile was fitted using the Laplace-Young equation to calculate the contact angle. The results showed that the contact angle of CS was 71.4 ± 1.94°, the contact angle of CS-SSOS was 84.0 ± 4.89°, and the contact angle of CS-SSOS-TPP was 91.3 ± 3.05°, indicating that the ternary composite particles changed from hydrophilic to hydrophobic and had a stronger adsorption capacity at the O / W interface.

[0143] (4) Infrared spectroscopy analysis: Vacuum-dried CS, CS-SSOS, and CS-SSOS-TPP samples were mixed with KBr at a ratio of 1:50 (g / g) and ground into fine powder, then pressed into tablets; Fourier transform near-infrared spectrometer was used for scanning, with a scanning range of 4000–250 cm⁻¹. -1 32 scans, 4cm resolution -1 The results showed that in CS-SSOS at 1560cm -1 The strong absorption peak at this point indicates that NH3 in the CS molecule... + With COO in SSOS - Electrostatic interactions occur; in CS-SSOS-TPP at 1590cm -1 An unreacted amino absorption peak appears at 1030 cm⁻¹. -1 A strong absorption peak for the stretching vibration of the PO bond appears at 3428 cm⁻¹. -1 The presence of a relatively broad spectral band confirms the existence of electrostatic interactions, hydrogen bonding interactions, and hydrophobic interactions between CS, SSOS, and TPP.

[0144] (5) XRD analysis: The freeze-dried CS, CS-SSOS, and CS-SSOS-TPP samples were ground into powder. 1g of the sample was scanned using an X-ray diffractometer. The scanning range was 5° to 60°, and the scanning speed was 0.05° / min. The test conditions were room temperature and Cu-Kα radiation. 30mA, 40kV. The results showed that CS had two main peaks at 2θ≈11.57° and 20.23°; the peak intensities of CS-SSOS and CS-SSOS-TPP composite particles both decreased, indicating that the introduction of SSOS and TPP suppressed the hydrogen bonds between amino and hydroxyl groups in CS, reduced the crystallinity of CS, and formed an amorphous structure.

[0145] (6) SEM Analysis: Solid samples of CS, CS-SSOS, and CS-SSOS-TPP were fixed on the scanning electron microscope stage with double-sided tape, covered with a gold film by sputtering, and observed and photographed under an accelerating voltage of 10 kV. The results showed that CS exhibited an irregularly fragmented sheet-like structure with an uneven surface; the CS-SSOS binary composite system exhibited a flat sheet-like structure; and the CS-SSOS-TPP ternary composite system formed a network with relatively dense pores, indicating that there was a strong interaction between the ternary composite particles and the structure was more compact and stable.

[0146] 2. Performance characterization of emulsions

[0147] (1) Particle size and particle size distribution: The emulsion was diluted with deionized water at a ratio of 1:200. The particle size and particle size distribution of the emulsion droplets were measured using a laser nanoparticle size analyzer at 25℃ and a scattering angle of 90°. Each sample was measured three times and the average value was taken. The results showed that when the oil phase fraction was 50%, the average particle size of the emulsion droplets was the smallest, at 3.8±0.17μm, and the particle size distribution was the most uniform.

[0148] (2) Centrifugal stability: Take 10 mL of freshly prepared emulsion, place it in a graduated centrifuge tube, centrifuge at 5000 r / min for 10 min, observe the phase separation, and calculate the centrifugal stability index (ES). The calculation formula is as follows: Where V cen V represents the volume of the emulsion phase remaining after centrifugation. Int The initial emulsion volume is given. The results show that the emulsion exhibits the highest centrifugal stability index and the strongest stability when the oil phase fraction is 50%.

[0149] (3) Rheological properties: The rheological properties of the emulsion were analyzed using a rheometer. A 40mm flat plate clamp was used, and an appropriate amount of emulsion was placed on the plate. The test temperature was 25±0.1℃. Steady-state shear tests were performed, with the shear rate starting from 0.1s. -1Increase to 100s -1 The viscosity changes were recorded; dynamic frequency scanning was performed, with the frequency increasing from 0.1 Hz to 10 Hz under a constant strain of 1%, and the storage modulus (G′) and loss modulus (G″) were recorded. The results showed that the emulsion exhibited obvious shear thinning behavior; when the oil phase fraction reached 50% or more, the viscosity of the emulsion increased significantly, and G′ > G″, indicating that the emulsion was mainly elastic with a compact and stable internal structure.

[0150] (4) Microscopic morphological observation: Take 10 μL of emulsion, spread it on a glass slide, cover it with a coverslip, and observe and photograph the morphology of the emulsion droplets using an optical microscope; observe the interface structure of the emulsion using a laser confocal microscope, stain the nanoparticles with fluorescein isothiocyanate (FITC), stain the oil phase with Nile red, and then drop 10-20 μL of the stained emulsion onto a glass slide, cover it with a coverslip, and observe. The results show that when the oil phase fraction is 50%, the emulsion droplets are evenly and densely distributed; CLSM images show that the oil droplets are wrapped with green fluorescence, indicating that the composite particles successfully encapsulate the oil droplets and form a stable O / W type emulsion system.

[0151] (5) Resistance to changes in ionic environment: NaCl was added to the emulsion at concentrations of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, and 0.5 mol / L, respectively. After thorough mixing, the droplet morphology was observed using an optical microscope, centrifugal stability was measured, and rheological properties were analyzed using a rheometer. The results showed that with increasing NaCl concentration, the droplet size did not change significantly and remained regularly spherical; centrifugal stability showed a slight decreasing trend; viscosity showed an increasing trend, but the emulsion still exhibited elastic behavior, indicating that the emulsion has a certain resistance to changes in ionic environment.

[0152] (6) pH responsiveness: The pH values ​​of the emulsion were adjusted to 1, 3, 5, 6, and 7, and after thorough mixing, the droplet morphology was observed using an optical microscope, the centrifugal stability was measured using centrifugation, and the rheological properties were analyzed using a rheometer. The results showed that as the pH increased to 6 and above, the emulsion droplets became larger and aggregated; the centrifugal stability first increased and then decreased, and the emulsion broke down at pH=7; under acidic conditions, the emulsion viscosity increased with increasing pH, while under neutral or slightly alkaline conditions, the viscosity first increased sharply and then decreased sharply, indicating that the emulsion has a certain pH responsiveness and good stability under acidic conditions.

[0153] 3. Performance evaluation of curcumin emulsion

[0154] (1) Storage stability: Five portions of curcumin emulsions with different concentrations were stored in a refrigerator at 4℃ in the dark for 30 days. At 0, 5, 10, 15, 20, 25, and 30 days of storage, 200 μL of the emulsion was taken out, and the curcumin concentration was determined spectrophotometrically. The curcumin retention rate was calculated using the following formula: Wherein C1 represents the curcumin concentration in the emulsions at different storage times, and C0 represents the curcumin concentration in the fresh emulsion. Simultaneously, the particle size change of the emulsions was measured periodically. The results showed that after 30 days of storage, the curcumin retention rate in all emulsions was above 70%, with the emulsion with an initial curcumin concentration of 500 mg / L exhibiting the highest retention rate of 86.9%. While all emulsion droplets showed some degree of aggregation, the overall structure remained stable, indicating that the emulsions effectively protected curcumin and improved its storage stability.

[0155] (2) Antioxidant activity: The antioxidant activity of the emulsion was determined using the DPPH method. A 1.0 mM DPPH working solution was prepared with ethanol. Freshly prepared emulsions and emulsions stored at 4℃ for 10, 20, and 30 days were diluted with distilled water. 1 mL of the diluted emulsion was added to 3.0 mL of the DPPH working solution, and after standing in the dark for 30 min, the absorbance was measured at 517 nm. The DPPH free radical scavenging rate was calculated using the following formula: Where A1 represents the absorbance of the blank control (sample without emulsion), A represents the absorbance of the emulsion sample, and A0 represents the absorbance of the blank control without DPPH. The results showed that curcumin at different concentrations in the fresh emulsion exhibited excellent antioxidant properties, with DPPH free radical scavenging rates all exceeding 80%. The scavenging rate increased with increasing curcumin concentration, reaching a equilibrium after reaching a certain concentration. With prolonged storage, the DPPH free radical scavenging rate gradually decreased, but after 30 days of storage, the free radical scavenging rate of the emulsion with an initial concentration of 500 mg / L was still 69.9%, indicating good antioxidant properties.

[0156] (3) In vitro digestion performance: Tested according to an in vitro digestion model. The dialysis bag was soaked in distilled water for 12 hours to remove preservatives and then rinsed with distilled water. 5.0 mL of curcumin emulsion was placed in the dialysis bag, sealed, and then immersed in 200 mL of simulated gastric juice (SGF, pH 1.2, containing 1 g / L sodium chloride and 0.15 g / L pepsin). It was incubated at 37°C and 100 rpm with magnetic stirring for 90 min. 3.0 mL of release medium was taken at 0 min, 30 min, 60 min, 90 min, and 120 min, and 3.0 mL of fresh simulated gastric juice was added simultaneously. After incubation, the dialysis bag was transferred to 200 mL of distilled water. The curcumin was incubated in simulated intestinal fluid (SIF, pH 6.8, containing 3.45 g / L disodium hydrogen phosphate, 2.25 g / L bile salts, 0.5 g / L trypsin, and 0.5 mM phosphate) at 37 °C with magnetic stirring at 150 rpm for 180 min. At 0 min, 30 min, 60 min, 90 min, 120 min, 150 min, and 180 min, 3.0 mL of release medium was collected, and 3.0 mL of fresh simulated intestinal fluid was added simultaneously. The concentration of curcumin in the release medium was determined spectrophotometrically at 420 nm, and the curcumin release rate was calculated. Curcumin aqueous solution was used as a control. The results showed that the loss rate of free curcumin was 39.6% after digestion in SGF for 120 min and 54.6% after digestion in SIF for 180 min. However, the release rate of curcumin emulsion after digestion in SGF for 120 min was less than 20%, while it was gradually and slowly released in SIF with a higher release rate than that in SGF. This indicates that the emulsion can protect curcumin from the destruction by SGF, achieve targeted and sustained release in the intestine, and is beneficial to the intestinal absorption of curcumin.

[0157] IV. Effects of Different Parameters on Emulsion Properties

[0158] 1. Effect of oil phase fraction on emulsion properties

[0159] Emulsions with oil phase volume fractions of 30%, 40%, 50%, 60%, and 70% were prepared with other preparation parameters remaining constant. The particle size, centrifugal stability, rheological properties, and microstructure of the emulsions were characterized. The results showed that as the oil phase fraction increased, the average particle size of the emulsion first decreased and then increased, reaching its smallest size at an oil phase fraction of 50%. The centrifugal stability index first increased and then tended to stabilize with increasing oil phase fraction, exhibiting the strongest stability at 50% oil phase fraction. Rheological tests indicated that as the oil phase fraction increased, the emulsion gradually transitioned from viscous behavior to elastic behavior, with the best elasticity and stability observed at 50% oil phase fraction. Microscopic observation showed that the emulsion droplet distribution was most uniform and dense at 50% oil phase fraction. Therefore, the optimal oil phase fraction was determined to be 50%.

[0160] 2. Effects of CS concentration on the properties of nanoparticles and emulsions

[0161] Ternary composite nanoparticle dispersions with different CS concentrations (0.5 mg / mL, 1 mg / mL, 1.5 mg / mL, and 2 mg / mL) were prepared with other preparation parameters unchanged. The particle size and Zeta potential of the nanoparticles were measured, and emulsions were prepared to determine their stability. The results showed that the nanoparticle size first decreased and then increased with increasing CS concentration, reaching its smallest value at a CS concentration of 1 mg / mL. The Zeta potential reached its highest value at a CS concentration of 1 mg / mL, and the corresponding emulsion stability was also optimal. Therefore, the optimal CS concentration was determined to be 1 mg / mL.

[0162] 3. Effect of curcumin concentration on emulsion properties

[0163] Emulsions with curcumin concentrations of 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L, and 700 mg / L were prepared with other preparation parameters unchanged. The rheological properties, microstructure, particle size distribution, and storage stability of the emulsions were characterized. The results showed that the apparent viscosity of the emulsions increased significantly after the addition of curcumin; the droplet distribution of the emulsions was finer and more uniform, and the particle size distribution showed a single peak; after 30 days of storage, the retention rate of curcumin at all concentrations was above 70%, with the highest retention rate and the best antioxidant activity at a concentration of 500 mg / L. Therefore, the optimal concentration of curcumin is recommended to be 500 mg / L.

[0164] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high temperature stable curcumin embedded sustained release Pickering emulsion characterized in that, consists of an aqueous phase, an oil phase and curcumin; the aqueous phase comprises chitosan-sodium octenyl succinate starch-sodium tripolyphosphate ternary composite nanoparticles, the mass fraction of chitosan, sodium octenyl succinate starch and sodium tripolyphosphate in the ternary composite nanoparticles in water is 1%, 0.84% and 0.08% respectively; the oil phase is corn oil, soybean oil or rapeseed oil, and the volume fraction of the oil phase is 50%; the curcumin is dissolved in the oil phase, and the concentration of curcumin in the oil phase is 300-700 mg / L; the emulsion is an O / W type emulsion, the average particle size of the emulsion droplets is 3.8±0.17 μm, and the retention rate of curcumin is ≥70% after storage for 30 days.

2. The high temperature qualified curcumin-embedded sustained release Pickering emulsion according to claim 1, characterized in that, the degree of deacetylation of the chitosan is ≥85%, and the purity of the curcumin is ≥95%; the contact angle of the ternary composite nanoparticles is 91.3±3.05°, and the microstructure is a reticular network with relatively dense pores; after the emulsion is digested in simulated gastric juice for 120 min, the release rate of curcumin is <20%, and after the emulsion is digested in simulated intestinal juice for 180 min, curcumin is released slowly.

3. A process for the preparation of high temperature stable curcumin embedded sustained release Pickering emulsion as claimed in any one of claims 1-2, wherein, comprises the following steps: Step one, preparation of chitosan-sodium octenyl succinate starch-sodium tripolyphosphate ternary composite nanoparticle dispersion; Step two, preparation of an oil phase dissolving curcumin; Step three, mixing of the ternary composite nanoparticle dispersion and the oil phase dissolving curcumin, emulsification and homogenization to obtain a Pickering emulsion; Step four, storage of the prepared emulsion at 4°C in the dark.

4. A process for the preparation of high temperature stable curcumin embedded sustained release Pickering emulsion as claimed in claim 3, wherein, Step one specifically comprises the following operations: (1) a certain amount of chitosan is weighed, dissolved in 2% (v / v) acetic acid solution, stirred until completely dissolved, and a cationic chitosan solution is obtained; (2) under ultrasonic assistance, a SSOS solution with a certain concentration is slowly added to the above chitosan solution, and after the addition is completed, stirring is continued for 10 min; (3) a TPP solution with a certain concentration is slowly added to the mixed solution, and after the addition is completed, ultrasonic treatment is performed for 30 min to obtain a ternary composite nanoparticle dispersion of the colloidal dispersion system; (4) the particle size, particle size distribution and Zeta potential of the nanoparticles are measured by a Zeta potential and particle size analyzer to ensure that the performance of the nanoparticles meets the requirements.

5. The process for the preparation of high temperature stable curcumin embedded sustained release Pickering emulsion as claimed in claim 3 wherein, Step two specifically comprises the following operations: (1) powdered curcumin is added to corn oil, soybean oil or rapeseed oil to achieve a concentration of 300-700 mg / L of curcumin in the oil phase; (2) the mixed system is placed on a magnetic stirrer and stirred for 6 h to ensure that the curcumin is fully dissolved; (3) the mixed system after stirring is placed in a centrifuge for centrifugal treatment to remove undissolved curcumin; (4) the upper clear oil phase dissolving curcumin is transferred to a brown glass bottle and stored in the dark for use.

6. The process for the preparation of high temperature stable curcumin embedded sustained release Pickering emulsion as claimed in claim 3 wherein, Step three specifically comprises the following operations: (1) the ternary composite nanoparticle dispersion and the oil phase dissolving curcumin are mixed according to a volume fraction of 50% of the oil phase to obtain a mixed system; (2) the mixed system is placed in a high-speed shearing emulsifier and stirred and dispersed at a speed of 12000 rpm for 2 min for preliminary emulsification; (3) The system after the preliminary emulsification was transferred to a homogenizer and homogenized at 13000 rpm for 2 min to obtain the Pickering emulsion with curcumin embedded; (4) The particle size distribution of the emulsion droplets was determined by a laser nanoparticle size analyzer, and the microscopic morphology and interface structure of the emulsion were observed by an optical microscope and a confocal laser scanning microscope; (5) The emulsion was determined to be an O / W emulsion by observing the diffusion of the emulsion droplets after stirring after the emulsion droplets were dropped into deionized water.

7. The process for the preparation of high temperature stable curcumin embedded sustained release Pickering emulsion as claimed in claim 3 wherein, In step four, samples were taken periodically during the storage of the emulsion, and the concentration of curcumin was determined by spectrophotometry to calculate the retention rate of curcumin; The preparation method further comprises a characterization step of the emulsion performance, specifically comprising: (1) The turbidity of the composite particles was determined by a UV-1800 spectrophotometer at 600 nm; (2) The contact angle of the composite particles was determined by a droplet shape analysis system; (3) Fourier transform near infrared spectrometer was used to analyze the infrared spectrum of the nanoparticles, scanning range 4000-250 cm -1 , scanning 32 times, resolution 4 cm -1 ; (4) The composite particles were subjected to XRD analysis by an X-ray diffractometer, with a scanning range of 5°-60° and a scanning speed of 0.05° / min; (5) The microscopic morphology of the composite particles was observed by a scanning electron microscope at an acceleration voltage of 10 kV; (6) Rheometer was used to analyze the rheological properties of the emulsion, shear rate 0.1-100 s -1 , frequency scanning range 0.1-10 Hz, test temperature 25±0.1℃; (7) The centrifugal stability of the emulsion was determined by a centrifugal method, with centrifugation at 5000 r / min for 10 min to calculate the centrifugal stability index ES; (8) The sustained-release performance of the emulsion was evaluated by an in vitro digestion model, with incubation in simulated gastric juice and simulated intestinal juice, and the curcumin release amount was determined by sampling periodically; (9) The antioxidant property of the emulsion was determined by a DPPH method, with determination of the absorbance at 517 nm to calculate the DPPH free radical scavenging rate.